Gekko (Gekko) dam, a new dark-colored tokay gecko from the Thai-Malay border (Squamata, Gekkonidae) - Meesook, Worawitoo; Jindamad, Tanasak; Toprai, Nittaya; Chotjuckdikul, Natthaphat; Supmee, Verakiat; Suppapan, Juthamas; Donbundit, Nattasuda; Sumontha, Montri; Pauwels, Olivier S. G. (Zootaxa, 2026)
We describe Gekko dam sp. nov. based on type specimens from a limestone hill in Palian District, Trang Province, southern peninsular Thailand. The new species is also found in Satun Province, southern peninsular Thailand, and in Perlis State, northwestern Peninsular Malaysia. A member of the subgenus Gekko, it differs from all currently recognized Gekko species by the following combination of morphological characters and pattern: maximal known snout-vent length of 149.1 mm, lack of contact between nostrils and rostral, 21–24 interorbital scales between supraciliaries, 72–83 scale rows around midbody, 12–14 dorsal tubercle rows at midbody, 26–28 ventral scale rows at midbody, 22 precloacal pores in males, two postcloacal tubercles on each side of the base of the tail, 14–17 subdigital lamellae on 1st toe and 19–21 on 4th toe, a Y-shaped mark on head, white spots on head, dark grey to black dorsal background with four regular bands of contrasting white spots on dorsum between limb insertions, throat and venter white with orange patches, and a copper iris.